ARTS-INTEGRATED LEARNING IN SCHOOL EDUCATION: ENHANCING CREATIVITY AND CRITICAL THINKING THROUGH PERFORMING ARTS - Singh, Pooja; Chandoria, Virender Kumar; Pandey, Chetna; Bhardwaj, Shiny; Pallavi; Tomer, Ritesh (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Arts-Integrated Learning (AIL) is a new pedagogical method which is a combination of artistic expression and academic learning to improve student learning outcomes. This paper explores how AIL, which is performed through performing arts, can help the school students develop their creativity and critical thinking. The research design is a mixed-method design with a quasi-experimental approach that includes control and experimental groups, in order to compare the application of the traditional methods of teaching with the arts-based ones. The surveys were in the form of structured surveys, observation in the classrooms and semi-structured interviews were used to collect data that was analyzed by both statistical and thematic methods. The results indicate that students in performing art programs like drama, music and dance prove to have much more creativity, critical thinking, engagement and better academic performance, when compared to students in standard classes. Adoption of performing arts promotes experiential learning, active participation and enhancement of conceptual learning. Moreover, qualitative pieces of information also emphasize on the enhanced abilities of communication, cooperation, and the motivation of the learners within the setting of arts integration. The research also focuses on the importance of teachers and institutional facilitation in the successful implementation of AIL. Although it may seem that the limitations encountered, i.e., the lack of resources and training, the findings indicate that the methods of arts-integration approach can be quite successful in changing the traditional teaching methods into the dynamic and student-centered learning experiences. The study is one among the many that are supporting the notion of interdisciplinary and experiential education, especially in the context of modern educational changes. In general, the analysis has shown that Arts-Integrated Learning is an effective instrument to develop higher-order cognitive abilities and promote a holistic in school teaching. The long-term effects of impact assessment and incorporation of digital technologies into arts-based pedagogy are the directions of future research.